Usefulness of Stereotactic Body Radiation Therapy for Treatment of Adrenal Gland Metastases - Cyrielle Scouarnec; David Pasquier; Joel Luu; Florence le Tinier; Loïc Lebellec; Erwann Rault; Eric Lartigau; Xavier Mirabel (Frontiers in Oncology, 2019)
Purpose: This study aimed to describe our institutional experience in the use of stereotactic body radiation therapy (SBRT) for the management of adrenal gland metastases from multiple primary cancers.Materials and Methods: We retrospectively reviewed 31 patients who underwent SBRT as treatment for 33 adrenal gland lesions in the academic radiotherapy department of Oscar Lambret cancer center between May 2011 and September 2018. The primary study endpoints were 1- and 2-year local control rates, defined as the absence of progression at the treatment site based on the response evaluation criteria in solid tumors (RECIST). Toxicities were graded in accordance with the Common Terminology Criteria for Adverse Events version 4.03.Results: The average tumor volume was 33.5 cm3 (standard deviation: 51.7 cm3), and the prescribed dose ranged from 30 to 55 Gy given in 3–9 fractions. The median biological effective dose was 112.5 Gy (range: 45–115.5 Gy), assuming α/β = 10. Considering progression at distant sites or death as competing events, the 1- and 2-year actuarial local control rates were 96.5% (95% confidence interval: 84.9–99.7) and 92.6% (95% confidence interval: 79.2–98.7), respectively. According to RECIST, a complete response was achieved in 10 (32.3%) lesions, a partial response in 10 (32.3%) lesions, and stability in 8 (25.8%) lesions. Three patients presented with local relapse at 8.8, 14, and 49.4 months. After a median follow-up of 18 months (range: 4.4–66.4), the median overall survival was 33.5 months (95% confidence interval: 17–not reached), while the median progression-free survival was 7.4 months (95% confidence interval: 3.8–14.1). Treatment-related toxicity was grade 1 or 2 in 42.4% of patients, including nausea (27.3%), abdominal pain (18.2%), vomiting (15.2%), and asthenia (9.1%). None of the patients developed acute grade ≥3 or late toxicity.Conclusion: SBRT seems to be a safe and effective treatment for adrenal gland metastases in patients whose primary tumor and metastatic spread are controlled by systemic treatment. With a 2-year local control rate of 92.6%, SBRT may be considered as one of the first-line treatments in oligometastatic patients with adrenal metastases.